The farming community in Jatinangor: A case study of business community on facing development challenges - Muttaqin, Zaenal; Gunawan, Wahyu; Sukoco, Iwan; Kusairi, Suhal (Edelweiss Applied Science and Technology, 2025)
Jatinangor has undergone a change in administrative status from a village to a city. This change is driven by the increasing development of community culture. This developmental challenge is strongly felt in the agricultural sector. This article aims to explain the continuous efforts of agricultural communities in facing various changes in Jatinangor to maintain the existence of agriculture in the area. The concept used is a change in development and the business community, which is reviewed from Giddens' structure. The method employed is a qualitative case study. This article finds that the existence of agriculture is still maintained despite the rapid changes in Jatinangor. In addition to local farmers, there are also immigrants who are interested in engaging in agricultural business and making a real contribution to the community, both in the development of agricultural technology and the supply of agricultural products to provide food for the community.